Action of probiotics, prebiotics and symbiotics on the gut microbiota of obese individuals - Andrade, Lorena Pinto; Oliveira, Franciele Florêncio de; Rosa, Gisele Gonçalves; Almeida, Flávia; Trindade, Aline Maíra Santos; Prado, Cassio Lucas Dias do; Ost, Luciana Vedia; Jordan, Vinícius Andrade (Seven Editora, 2023)
Obesity is a chronic disease that corresponds to excess accumulated fat, has a multifactorial etiology, and is a risk factor for other chronic pathologies. Changes in the diversity and composition of the gut microbiota are increasingly associated with various disease states, including obesity and behavioral disorders. Evidence shows that in obese individuals there are more bacteria of the phylum Firmicutes, than in a person with eutrophic weight, there is more imbalance of the microbiota influenced by the increase in the energetic extraction of the components of the diet, lipogenesis, and intestinal permeability. Thus, studies have shown therapeutic action through intestinal modulation with functional foods, using probiotics, prebiotics and symbiotics, since it is necessary to reduce the public costs assigned to obesity. This work aims to describe the action of probiotics, prebiotics and symbiotics along with a balanced diet for obese adults. This is a systematic review of the literature conducted with publication in the period from 2011 to 2021, which used as database the Medical Literature Analysis and Retrieval System Online (Pubmed), Scientific Electronic Library Online (Scielo) and Virtual Health Library (VHL). In the studies evaluated, the most used strains and concentrations were Bifidobacterium and Lactobacills at 1010 CFU/g. With the results of decreased body composition such as body fat mass, waist circumference, energy intake and body weight and that the use of these supplements can modulate the human gut microbiota, increasing potentially beneficial microbial species. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-167